PENGARUH KOMPETENSI, DISIPLIN KERJA DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK PROVINSI RIAU - Soleha Sri Wijayanti Ina; Roesdy Rosnelly; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The Central Statistics Agency of Riau Province is one of the representativeinstitutions of the Central Statistics Agency in the regions which has the maintask of providing basic statistical data in accordance with the provisions ofapplicable laws and regulations. This research was conducted at the CentralBureau of Statistics Jalan Patimurra No. 12 Pekanbaru, Riau. The purpose of thisstudy was to determine the effect of competence, work discipline and training onemployee performance. This type of research is quantitative. The population inthis study were 82 employees of the Central Statistics Agency of Riau province.The sample in this study was the entire population, amounting to 82 people. Thesampling method used in this study is non-probability sampling. This study usesmultiple linear regression analysis using SPSS 23. The results of this studyindicate that competence has a positive and significant effect on performance,work discipline has a positive and significant effect on performance, and thetraining variable has a positive and significant effect on performance. Meanwhile,simultaneously the variables of competence, work discipline and training have apositive and significant effect on employee performance. Keywords: Employee Performance, Competence, Work Discipline, Training